Students’ Experiences and Perceptions of Interprofessional Supervision on Placement - Yang, Kizzy; Nisbet, Gillian; McAllister, Lindy (International Journal of Practice-based Learning in Health and Social Care, 2017)
This study aimed to explore perceptions and experiences of Occupational Therapy and Speech-Language Therapy students regarding interprofessional supervision during an interprofessional rural schools placement. Eight participants were recruited to participate in three semi-structured, one-to-one interviews conducted by phone before, during, and after the placement. The interviews were transcribed verbatim for subsequent thematic analysis. Our findings indicate that whilst participants valued the interprofessional peer supervision afforded by interprofessional placements, they entered interprofessional placements with misguided assumptions and expectations regarding interprofessional supervision from supervisors. This appeared to contribute to their largely negative perceptions of interprofessional supervision resulting in the devaluing of interprofessional supervision now and possibly in the future. This exploratory study presents a unique insight into the limitations of interprofessional supervision, and the critical need for interprofessional supervisor training and student preparation before placements. Follow-up research is required to expand on these findings so the limitations are addressed. This may enable interprofessional supervisors to provide better learning experiences, increasing students’ acceptance and appreciation of interprofessional supervision.